REPRESENTATION OF CULTURAL VALUES IN THE FILM THE ARCHITECTURE OF LOVE (2024) IN THE VIEW OF KLUCKHOHN AND STRODTBECK - Parasian, Nehemia Anugrah; Perangin-angin, Alemina Br. (Metahumaniora, 2025)
This research explore explores the representation of cultural value orientations in the film The Architecture of Love using Kluckhohn and Strodtbeck’s theoretical framework. The research focuses on five key dimensions of cultural values: human nature, man-nature, time, activity, and relational orientations. Employing a qualitative descriptive method, this study analyzes selected scenes and dialogues from the film to identify implicit and explicit cultural meanings. The findings reveal that the film portrays human nature as dynamic and emotionally complex, emphasizing individual capacity for healing and growth. The relationship between human and nature is shown through symbolic interactions with urban architecture, suggesting a harmonious coexistence with the environment. The man-nature orientation is reflected in the characters’ symbolic relationship with urban architecture as a living space imbued with memory, emotion, and personal transformation, suggesting a harmonious interaction between human experiences and the built environment. Time orientation is reflected through characters’ struggles with past trauma and their efforts to reconstruct the future. Activity orientation emerges as a transformation from emotional passivity to active engagement with life. Most prominently, relational orientation is manifested through strong social bonds, where emotional recovery is facilitated by familial and communal support. These values are represented not as isolated traits, but as interrelated dimensions embedded in character development and narrative progression. This research contributes to a deeper understanding of how cultural ideologies are constructed and conveyed through cinematic narratives, offering insights into the intersection of culture, emotion, and identity in contemporary film.